Lucky You: Your Case is Heard by a Seasoned Panel - Panel Effects in the German Constitutional Court - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2021)
The German Constitutional Court is radically different from the (mostly US) courts in which panel effects have been studied so widely. On the one hand, to a large extent, ideological and gender bias are neutralized by design. On the other hand, panels are not randomly composed. This makes it possible to study a panel effect that has escaped attention. It results from the degree of familiarity among the judges on the bench. The longer their joint experience on the bench, the higher the chances that a complaint is successful. Regression discontinuity allows for a causal interpretation, at least near regular, exogenous recompositions of the bench.
Keywords: C12; D71; D73; D91; H11; K41; 330; panel effect; German Constitutional Court; familiarity; regression discontinuity